Abnormally weak intervalley electron scattering in MoS2 monolayer: insights from the matching between electron and phonon bands. Issue 33 (8th August 2022) - Song, Shiru; Yang, Ji-Hui; Gong, Xin-Gao
Abstract : Electron mobility decreases abnormally from monolayer to bulk MoS2 due to smaller electron–phonon intervalley scattering in the monolayer. Abstract : It is known that carrier mobility in layered semiconductors generally increases from two-dimensions (2D) to three-dimensions due to fewer scattering channels resulting from decreased densities of electron and phonon states. In this work, we find an abnormal decrease of electron mobility from monolayer to bulk MoS2 . By carefully analyzing the scattering mechanisms, we can attribute such abnormality to the stronger intravalley scattering in the monolayer but weaker intervalley scattering caused by few intervalley scattering channels and weaker corresponding electron–phonon couplings compared to the bulk case. We show that it is the matching between the electronic band structure and phonon spectrum rather than their densities of electronic and phonon states that determines scattering channels. We propose, for the first time, the phonon-energy-resolved matching function to identify the intra- and inter-valley scattering channels. Furthermore, we show that multiple valleys do not necessarily lead to strong intervalley scattering if: (1) the scattering channels, which can be explicitly captured by the distribution of the matching function, are few due to the small matching between the corresponding electron and phonon bands; and/or (2) the multiple valleys are far apart in the reciprocal space and composed of out-of-plane orbitals so that the corresponding electron–phonon coupling strengths are weak. Consequently, the searching scope of high-mobility 2D materials can be reasonably enlarged using the matching function as useful guidance with the help of band edge orbital analysis.